MIGRATING ON-PREM DATA WAREHOUSING TO MICROSOFT FABRIC: LESSONS LEARNED AND BEST PRACTICES - Mahesh Thoutam, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article explores the complex process of migrating on-premises data warehousing to Microsoft Fabric, a comprehensive cloud analytics platform. It examines the key drivers behind cloud adoption in data management, including scalability, cost-efficiency, and advanced analytics capabilities. The article delves into the major challenges organizations face during migration, such as data transfer complexities, integration with existing systems, and ensuring data security and compliance. It provides best practices for successful migration, including conducting thorough pre-migration assessments, choosing the right migration strategy, leveraging Microsoft Fabric's advanced features, and prioritizing testing and optimization. A real-world case study of a global life sciences company's cloud migration illustrates these concepts in practice, demonstrating significant improvements in operational efficiency, scalability, and innovation.